Nuclei DNA Damage Due to Extreme High-Temperature Exposure during Forensic Identification Examination - Ahmad Yudianto; Masniari Novita; Ariyanto Wibowo; Fery Setiawan (Faculty of Medicine, Universitas Padjadjaran, 2020)
Accurate personal identification is important in investigations because an error in the identification process may bring fatal consequences during trial. The most common identification process is the Deoxyribonucleic acid [DNA] analysis. Degraded DNA sample due to extremely high-temperature exposure may limit DNA analysis. This study aimed to analyze DNA damage patterns caused by an extremely high temperature using STR (short tandem repeat) CODIS marker. This study was conducted at the Forensic and Medicolegal Department, Laboratorium Balai Besar Kesehatan Surabaya, Ministry of Health of the Republic of Indonesia, Human Genetic Study Group of Universitas Airlangga, and Faculty of Science and Technology of Universitas Brawijaya Malang from July until October 2009. Results of PCR visualization using STR CODIS for costae demonstrated that the THO1 detection (+) in 1,2500C - 40’: 25% and the TPOX detection (+) in 1,0000C - 30’: 50% whereas the results from molar teeth showed that the THOI locus detection (+) in 1,2500C - 30’: 25% and TPOX in 1,0000C - 40’: 50%. Results for PCR visualization using mini-STR CODIS for the costae presented that the mini-THOI in 1,2500C - 20’: 50% (+) while for the molar tooth the mini-THOI in 1,2500C - 30’ : 25% (+) and mini-TPOX in 1,0000C - 40’ : 50% (+). All loci were detected on costae and second molar teeth samples of the control group. Thus, extreme high-temperature exposure significantly decreased the DNA level of second costae and second molar tooth. Sequence patterns of STR loci successfully detected were TPOX, THO1, and CSF1PO.Kerusakan DNA Inti Karena Paparan Suhu Tinggi Selama Proses Identifikasi ForensikIdentifikasi melalui DNA secara tepat penting dalam penyelidikan karena kesalahan akan berakibat fatal selama proses persidangan. Salah satu keterbatasan adalah DNA yang terdegradasi karena paparan suhu yang sangat tinggi. Penelitian ini bertujuan menganalisis pola kerusakan DNA akibat suhu sangat tinggi menggunakan penanda CODIS STR (short tandem repeat). Penelitian dilakukan di Instalasi Kedokteran Forensik, Laboratorium Kemenkes, Human Genetic Study Group, dan Universitas Brawijaya Malang pada periode Juli sampai Oktober 2009. Visualisasi PCR menggunakan STR CODIS untuk costae adalah sebagai berikut: deteksi THO1 (+) pada 12500C - 40’: 25%, deteksi TPOX (+) pada 10000C - 30’: 50%, sedangkan hasil dari gigi molar adalah sebagai berikut: THOI locus detection (+) di 12500C - 30’: 25% dan TPOX di 10000C - 40’: 50%. Hasil visualisasi PCR menggunakan mini-STR CODIS untuk costae adalah sebagai berikut: mini-THOI pada 12500C - 20’: 50% (+) dan untuk gigi molar: mini-THOI pada 12500C-30': 25% (+ ) dan mini-TPOX di 10000C - 40’ : 50% (+). Semua lokus terdeteksi pada kelompok kontrol pada sampel costae dan gigi molar kedua. Kesimpulannya, paparan suhu tinggi yang ekstrim secara signifikan menurunkan tingkat DNA kosta dan gigi molar kedua.